Does Education Reduce Wage Inequality? Quantile Regressions Evidence from Fifteen European Countries - Pedro Telhado Pereira; Pedro Silva Martins (Institute for the Study of Labor (IZA), 2000)
We address the impact of education upon wage inequality by drawing on evidence from fifteen European countries, during a period ranging between 1980 and 1995. We focus on within-educational-levels wage inequality by estimating quantile regressions of Mincer equations and analysing the differences in returns to education across the wage distribution and across time. Four different patterns emerge: 1) a positive and increasing contribution of education upon within-levels wage inequality ?the case of Portugal; 2) a positive but stable role of education in terms of inequality – Austria, Finland, France, Ireland, Netherlands, Norway, Spain, Sweden, Switzerland, UK; 3) a neutral role – Denmark and Italy; and 4) a negative impact – Germany and Greece. We thus find that in most countries dispersion in earnings increases with educational levels and that education is a risky investment. These results suggest a positive interaction between schooling and ability with respect to earnings.
Keywords: D31; C29; J31; J24; I21; 330; Returns to education; earnings inequality; quantile regressions; ability; education systems; labour-market institutions; Lohnstruktur; Bildungsinvestition; Bildungsertrag; Arbeitsmarkt; Schätzung; Portugal; Österreich; Finnland; Frankreich; Irland; Niederlande; Norwegen; Spanien; Schweden; Schweiz; Großbritannien; Dänemark; Italien; Deutschland